2020
DOI: 10.1155/2020/4946954
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Graphene Oxide by Laser Scribing in Different Atmospheres and Application in Humidity Sensing

Abstract: Laser scribing, by far proposed as a method for efficiently transforming graphene oxide into reduced graphene, has been employed, using a CW laser beam, to study the modifications of graphene oxide scribed under different controlled atmospheres, including air, N2, Ar, and a 95 : 5 (v/v) Ar/H2 mixture. We have found that laser scribing effects, including chemical composition, order degree, and electrical properties, strongly depend upon the atmosphere during the irradiation. The electrical properties of the var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…In our previous work [17], we demonstrated that the scribing environment is a key factor in achieving high-quality RGO and that Argon-based atmospheres yield the best outcome in terms of similarity of RGO to pristine graphene. In this paper, we determine the best materials and processing conditions to achieve the best possible RGO quality by investigating parameters such as scribing speed, amount of material, and number of scribing passes.…”
Section: Introductionmentioning
confidence: 98%
“…In our previous work [17], we demonstrated that the scribing environment is a key factor in achieving high-quality RGO and that Argon-based atmospheres yield the best outcome in terms of similarity of RGO to pristine graphene. In this paper, we determine the best materials and processing conditions to achieve the best possible RGO quality by investigating parameters such as scribing speed, amount of material, and number of scribing passes.…”
Section: Introductionmentioning
confidence: 98%
“…It was found that the highest ΔR/R (~10%) was given by rGO obtained in argon, with the lowest hysteresis. The system showed a response and recovery as fast as that of a commercial RH sensor, but it was only responsive between 0% and ~15% RH [52].…”
Section: Humidity Sensingmentioning
confidence: 96%
“…The system showed a detection limit around 6% RH and very fast response (2 s) and recovery (4 s) time [55]. RH response from rGO obtained under different controlled atmospheres (air, N2, Ar, Ar/H2) was also investigated [52]. It was found that the highest ΔR/R (~10%) was given by rGO obtained in argon, with the lowest hysteresis.…”
Section: Humidity Sensingmentioning
confidence: 99%
See 2 more Smart Citations